The Negation of Divinity in View of Human Emancipation: Nurcholish Madjid Perspective - Dimas Prihambodo; Muhammad Kharis Tambusai (Journal of Comparative Study of Religions, 2022)
The RUU HIP is an abbreviation of the Rancangan Undang Undang Haluan Ideologi Pancasila (the Draft Law on Pancasila Ideology). The RUU was proposed by the DPR RI, Badan Legislatif Dewan Perwakilan Rakyat Republik Indonesia (the Legislative Body of the House of Representatives of the Republic of Indonesia). In its development, there was resistance from various groups which led to demonstrations from social groups or organizations. One of the criticisms is the reduction in the value of Pancasila which can lead to the de-emancipation of the Indonesian nation. The conclusion obtained is that the RUU HIP contains efforts to reduce divine values and only leaves human values, namely mutual cooperation. In addition, the interpretation carried out contains inconsistencies, disorientation, and the disintegration of Pancasila. Therefore, the efforts made will depart from the good goals that have been formulated. So that the expected emancipation will be inversely proportional to the de-emancipation of the Indonesian nation.